Enhancing pastoralists' resilience in livestock value chains in East Africa - Godana, Racho; Agolla, Frankline; Mwikya, John (Technical Centre for Agricultural and Rural Cooperation, 2018)
The remote arid and semi-arid Lands of Northern Kenya are dominated by pastoralist livestock production and are constantly threatened by prolonged droughts. Destocking, restocking and moving their herd to grazing areas are a key coping strategy for herders. Yet in times of stress, herders often find themselves selling stock at low prices. The challenge of accessing information serves is a key constraint for pastoralist communities to make informed decisions and manage risks.